2006
DOI: 10.1021/jp056851g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Monoalkyl Glycoside Micelles in Aqueous Solution:  Influence of Carbohydrate Headgroup Stereochemistry

Abstract: Comparative molecular dynamics simulations of n-octyl-beta-D-galactopyranoside (beta-C8Gal) and n-octyl-beta-D-glucopyranoside (beta-C8Glc) micelles in aqueous solution have been performed to explore the influence of carbohydrate stereochemistry on glycolipid properties at the atomic level. In particular, we explore the hypothesis that differences in T(m) and T(c) for beta-C8Gal and beta-C8Glc in lyotropic systems arise from a more extensive hydrogen bonding network between beta-C8Gal headgroups relative to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 51 publications
8
46
1
Order By: Relevance
“…The lower 〈 f tail 〉 values of GLYCAM06 indicate that for those micelles the surfactant alkyl chains of the micelle are more protected from the solvent than those obtained in the simulations with the CHARMM force fields. In comparison, the 〈 f tail 〉 values reported in this work are lower than those found by Stephenson et al 51 for a micelle with 45 β-C 12 G 2 (∼17.0 %), and also lower than for micelles with 27 octyl-β-galactose47 (∼30%) and 92 octyl-β-glucose monomers (20%) 46. The latter is probably due to the smaller size of the headgroup in those micelles, which shields less the micelle hydrophobic core from water.…”
Section: Resultscontrasting
confidence: 80%
See 3 more Smart Citations
“…The lower 〈 f tail 〉 values of GLYCAM06 indicate that for those micelles the surfactant alkyl chains of the micelle are more protected from the solvent than those obtained in the simulations with the CHARMM force fields. In comparison, the 〈 f tail 〉 values reported in this work are lower than those found by Stephenson et al 51 for a micelle with 45 β-C 12 G 2 (∼17.0 %), and also lower than for micelles with 27 octyl-β-galactose47 (∼30%) and 92 octyl-β-glucose monomers (20%) 46. The latter is probably due to the smaller size of the headgroup in those micelles, which shields less the micelle hydrophobic core from water.…”
Section: Resultscontrasting
confidence: 80%
“…This finding has been observed in the various MD simulations performed in this study, regardless of the force field. Finally, in contrast with previous simulations 46,47 of octyl-β-glucoside micelles, the integrity of the micelles studied with the GLYCAM and CHARMM force fields is maintained all along our simulation time window (14 ns), and no surfactant molecules escaped from the micelle. This is consistent with previous experimental results obtained for alkyl-maltoside micelles where it was found that monomer exchange between micelle and the solvent is in the order of 0.1 to 1.2 μs 89…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Similar results have been observed for alkylmonoglucoside surfactants (i.e. C 10 G 1 and C 8 G 1 ), suggesting that this network could explain the thermal stability and cryoprotective effects of these surfactants [31,32].…”
Section: Micellar Sizesupporting
confidence: 80%